THE RELATIONSHIP OF PSYCHOLOGICAL AND PHYSICAL IMPACTS ON DRUG ABUSE TO ORAL AND DENTAL HYGIENE - Indraswari Wahyu Pertiwi; Riky Hamdani; Galuh Dwinta Sari; Isnur Hatta; Irham Taufiqurrahman (Universitas Lambung Mangkurat, 2024)
Background: Drug usage can have a negative psychological and physical influence on dental hygiene. Drug abusers' low priority for oral and dental health is linked to behavioral changes, needle phobia, and dread of the dentist, all of which are part of the psychological impact of drug usage. Poor dental and oral hygiene in drug users can be attributed to reduced motor function, which is part of the physical side effects of drug use. Objective: To analyze the psychological and physical impact of drug abuse on oral hygiene at IPWL Griya Pemberdayaan Banjarbaru city. Methods: Using an analytic observational study using a cross-sectional method and a basic random sample strategy. The population of drug users in the IPWL Griya Pemberdayaan Banjarbaru city was 50 persons, and a sample of 38 people was acquired. The WHOQOL-Bref questionnaire was utilized in this study to assess the psychological and physical effects of drug misuse, as well as the OHI-S index criteria to assess dental and oral hygiene status, which were then analyzed using the Spearman test. Results: The Spearman test showed that there is a relationship between the psychological impact of drug abuse on oral hygiene with a strong weak correlation, and there is a relationship between the physical impact of drug abuse on oral hygiene with a fairly strong correlation. Conclusion: it is necessary to improve dental and oral hygiene to reduce the psychological and physical impact of drug abuse.